Airlines Seat Pricing with Seat Upgrading - Yihua Li; Ahmadreza Mahmoudzadeh; Xiubin Bruce Wang (Multimodal Transportation, 2022)
Pricing optimization is key to the airlines’ profitability. Oftentimes, the premium cabin demand falls short of the seat capacity, making economy cabin seat upgrading a common practice. The common procedure in the airline industry solves the revenue management optimization for premium cabin first and then to determine the number of seats left for lower cabin upgrading, which together with the lower cabin seat capacity, allows to solve the lower (economy) cabin optimization. In comparison, this paper develops models to combine all the cabin capacities, including economy and premium (business/first), and solve the optimization simultaneously. The models consider cases with deterministic and random demand, respectively. Numerical tests use actual production data and indicate that the proposed models outperform the current ones in practice.